MARKET CONCENTRATION AND PERFORMANCE OF GENERAL HOSPITALS IN POLAND - Łyszczarz, Błażej (Ekonomia i Prawo. Economics and Law, 2014)
Theories of the hospital market view hospitals as competing for patients, physicians and third-party payers simultaneously. The competition involves such elements as price, quality, convenience, technology and innovation and the effects of the competition in the market affect the quality of care, clinical outcomes, cost of services, access as well as patient satisfaction. The purpose of the paper is to shed some light on the impact of competition on the performance of general hospitals in Poland. Due to the unavailability of micro-level data, territorial concentration based on regional data is used as a proxy for the scope of competition. Therefore, the territorial concentration of hospital beds is measured with the use of the Herfindahl-Hirschman index (HHI) for each of the 16 provinces of Poland and for the four-year period of 2008-2011. In the second stage, the values of the concentration index are correlated with a set of variables describing the performance of hospitals. The results show that the concentration of hospital beds in the regions is uneven. The regions with the most concentrated markets (zachodniopomorskie, łódzkie, podlaskie and mazowieckie) are characterized by four times higher values of the HHI than the one with the least concentrated market (śląskie). The results suggest that a higher concentration in the hospital market correlates with a larger number of patients treated and an increase in the cost of services.